Product Quality, Price Perception, Customer Loyalty on IM3-Indosat SIM Card's Users - Ardiansyah, Tri Endi; Dara, Nursimah; Nasution, Doni Alnis (International Journal of Management and Business Intelligence, 2024)
This study aims to examine the impact of Product Quality and Price Perception on Customer Loyalty. The research is quantitative and employs a survey methodology. The sample consists of 100 respondents. Primary data was analysed using SPSS version 26 for evaluation. The analysis results indicate that both Product Quality and Price Perception have a positive and significant influence on Customer Loyalty, with a significance value of 0.000 less than 0.05 and F-count of 146.348 greater that F-table 3.09. The coefficient value shows that 75.1% of Customer Loyalty is explained by Product Quality and Price Perception. These findings confirm the initial hypothesis, demonstrating a positive and significant effect of Product Quality and Price Perception on Customer Loyalty at 75.1%.